Field measurement study on time-varying characteristics of modal parameters of super high-rise buildings during super typhoon. Issue 200 (May 2020) - Zhang, Lele; Hu, Xiaoqi; Xie, Zhuangning; Shi, Biqing; Zhang, Li; Wang, Ronghui
Abstract: This study identifies the modal parameters of four super high-rise buildings in Shenzhen and analyzes the variation of their structural dynamic properties with amplitude and time based on the long-term field data of Super Typhoon Mangkhut. Results show the maximum acceleration of the four buildings is 13.29–41.96 milli-g and occurs at the maximum wind speed period. In the early stage, as the wind speed increases with time, structural modal frequencies decrease and reach the minimum during the maximum wind speed period. Subsequently, wind speed gradually decreases, modal frequencies increase slowly, and the highest ratio of frequency change is 11.9%. The change of damping ratio is somewhat stochastic but overall first increases and then decreases with time. The mode shapes of most buildings remain basically unchanged during typhoon. However, the mode shapes of the building with the maximum response differ greatly at the maximum and the low wind speeds. Besides, the two-order modal frequencies drop sharply near the maximum wind speed and approach one another to an indistinguishable degree. These new results and rules of modal parameters have important reference values for the further research on the influence of wind–structure interaction on structural wind effect and subsequent wind-induced vibration control. Highlights: The mode shape of the building with maximum response changes greatly at different wind speeds, showing obvious WSI effect. Modal frequencies first decrease and then increase with time and reach the minimum near the maximum wind speed. Two-order modal frequencies of the building with maximum response approach one another to an indistinguishable degree. The damping ratio first increases and then decrease with time.